A 0-1 Goal Programming Model for Easy book Staff Scheduling at Tawau Bus Terminal, Sabah - Asdalifah Talibe; Sarina Sirajuddin (Faculty of Science & Natural Resources, UMS, 2022)
This paper discusses on development of a 0-1 goal programming model and to schedule the Easybook staff at the Tawau Bus Terminal, Tawau, Sabah. The constraint of the model is based on the tasks given by Easybook which represent a hard constraint while the demands and needs of staff as a soft constraint. Then, the model will be applied in LINGO to produce an optimal schedule. There are four priority levels in this paper, and each will be solved one by one to find out whether the level of priority can be archived or not. From the schedule, all the goals and constraints have been achieved completely.